Design of the Muhammadiyah University of Madura Campus in Sampang Regency with Biophilic Architecture Approach - Rus Armi, Zaqi Islammaulana; Gunawan, Gunawan; Rofi'i, Rofi'i (Universitas Indraprasta PGRI, 2025)
The Muhammadiyah organization is the oldest Islamic organization that still exists in Indonesia with the